The effects of organizational culture on expatriates and repatriates’ cross-cultural adjustment, general satisfaction and withdrawal intentions - Pinto, Luisa Helena Ferreira (2008)
Tese de Doutoramento em Ciências Empresariais - área de Organização e Políticas Empresariais